Sustainable management of plastic waste: Assessment of recycled biodegradable plastic market and projection for the future - Adekomaya, Oludaisi; Majozi, Thokozani (Engineering and Applied Science Research, 2020)
Global production of plastics has increased astronomically in the last five decades. This may not be unconnected with the rate of consumption of plastics owing to their increasing applications and good characteristics such as light weight, strength, durability, affordability, corrosion resistance and low production costs. Production of plastic materials accounts for 3 to 5% greenhouse gas (GHG) emissions globally. Reports from published works show that, as of 2015 alone, close to 6300 metric tonnes of synthetic plastic waste were generated, of which only 9% were recycled with 12% being incinerated, and a large proportion, 79%, discarded in the natural environment. Further studies show that a sizeable proportion, 12,000 metric tonnes, of plastic waste may annually find their way into the environment by 2050. The adoption of biodegradable materials to replace the conventional plastics has been proposed and implemented with varying environmental implications. In this paper, a sustainable approach to plastic wastes was examined, taking into consideration the emerging and developing world’s attitudes about plastic waste management. Also discussed in this paper is the projection of the plastic waste market with particular reference to United States and China as global players in the industry. The concluding part of this paper focuses on future trends in plastic innovation with the evolution of nanoscale materials, bio-refining and most importantly cradle-to-cradle packaging materials. It is expected that this paper will assist various bodies involved in plastic waste management for developing better and sustainable methods.